PROJECTS AND OPERATIONS IN THE OIL AND GAS E&P SEGMENT: A BIBLIOGRAPHIC PANEL - de Castro, Jose Francisco Tebaldi; Lima, Claudio Benevenuto de Campos; Gutierrez, Ruben Huamanchumo (Brazilian Journal of Operations & Production Management, 2015)
This article provides a better understanding from the literature on the multi-disciplinary processes management and on large critical projects, in multiple environments, in an oil operator. A bibliographic panel was prepared, from a bibliometric research, focusing on portfolio, projects, operations and resources. The analysis of the literature was made from the perspective of integration of processes, taking as fundaments their interdependencies and multidisciplinary aspects. There was no evidence that integration is a reality in processes so large and multi-disciplinary, as well as in multiple environments with large projects. However, good practices were found and they are related to isolated cases. This study identified and separated issues that are inherent to the studied processes, from the ones that are result of poor integration and immaturity of the processes which are of vital importance for the construction of an integrated and multidisciplinary model. This article takes a critical look on how the treatment of such aspects add value through the identification of the interfaces, that are important in organizations that operate in multiple environments projects, together with production operations.